Efektivitas Penjatuhan Pidana Mati Terhadap Pelaku Tindak Pidana Narkotika - Zulfa Asma Vikra (al-Battar: Jurnal Pamungkas Hukum, 2024)
This study aims to determine the urgency of imposing the death penalty against narcotics offenders and the effectiveness of imposing the death penalty in overcoming narcotics crimes in the jurisdiction of the Banjarmasin District Court. This research uses empirical legal research, namely research on primary data and secondary data. Primary data is obtained through written observations and interviews. While secondary data in the form of primary, secondary and tertiary legal materials collected by literature study. Then the data is processed and analyzed qualitatively. The results showed that the death penalty is still needed in the context of overcoming narcotics crimes, because the death penalty will have a psychological impact on the community not to commit narcotics crimes. Then the imposition of death penalty by the Banjarmasin District Court is less effective in the context of overcoming narcotics crimes.